Organic Reactions 2019
DOI: 10.1002/0471264180.or100.09
|View full text |Cite
|
Sign up to set email alerts
|

Suzuki–Miyaura Cross‐Coupling

Abstract: The Suzuki–Miyaura cross coupling reaction uses a metal catalyst to create carbon–carbon bonds from organoboron reagents and organo(pseudo)halides. By careful adjustment of the ligand system, solvents, and other additives, this reaction can couple a diverse range of sp‐, sp 2 ‐, and sp 3 ‐hybridized organoboron and organo(pseudo)halide reactants. The Suzuki–Miyaura cross coupling reaction has become preeminent in both small‐ and large‐scale synthesis owing to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 298 publications
0
32
0
Order By: Relevance
“…The radiosynthesis of [ 11 C]UCB‐J is based on the application of the palladium(0)‐mediated Suzuki cross‐coupling reaction between the carbon‐11 methyliodide ([ 11 C]CH 3 I) and trifluoroborate precursor 3 (Figure ) . Initially explored method employed a more common Suzuki reacting partner, ie, the corresponding boronic acid (eg, 4 in Scheme ) as a radiolabelling precursor; however, the boronic acid precursor 4 proved to be unstable upon storage resulting in poor reproducibility and unreliable radiochemical yields. Further investigation indicated that while trifluoroborate 3 can be used as a radiolabelling precursor for [ 11 C]UCB‐J, the actual reacting specie is the boronic acid, thus necessitating a need for a mixture of trifluoroborate 3 and 3‐10% of the boronic acid 4 to be present in the reaction vessel …”
Section: Resultsmentioning
confidence: 99%
“…The radiosynthesis of [ 11 C]UCB‐J is based on the application of the palladium(0)‐mediated Suzuki cross‐coupling reaction between the carbon‐11 methyliodide ([ 11 C]CH 3 I) and trifluoroborate precursor 3 (Figure ) . Initially explored method employed a more common Suzuki reacting partner, ie, the corresponding boronic acid (eg, 4 in Scheme ) as a radiolabelling precursor; however, the boronic acid precursor 4 proved to be unstable upon storage resulting in poor reproducibility and unreliable radiochemical yields. Further investigation indicated that while trifluoroborate 3 can be used as a radiolabelling precursor for [ 11 C]UCB‐J, the actual reacting specie is the boronic acid, thus necessitating a need for a mixture of trifluoroborate 3 and 3‐10% of the boronic acid 4 to be present in the reaction vessel …”
Section: Resultsmentioning
confidence: 99%
“…In the former case, the nature of the Pd complex that activates the competing aryl chloride substrates can be studied during the oxidative addition to a Pd(0) compound, which results in the formation of an ArPdX-type intermediate. 3 In the latter case, the DS patterns of the competing arylboronic acids will characterize the nature of the Pd complex that reacts with the competing arylboronic acids; this occurs through transmetalation of the arylpalladium complexes with the arylboronic acids. Therefore, using these possibilities, a wide set of experimental data can be obtained, leading to further evidence for the obtained conclusions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Under Suzuki-Miyaura reaction conditions, it is possible to conduct the experiments using two essentially different competitions between two aryl halides or two arylboronic acids. In the former case, the nature of the Pd complex that activates the competing aryl chloride substrates can be studied during the oxidative addition to a Pd(0) compound, which results in the formation of an ArPdX-type intermediate . In the latter case, the DS patterns of the competing arylboronic acids will characterize the nature of the Pd complex that reacts with the competing arylboronic acids; this occurs through transmetalation of the arylpalladium complexes with the arylboronic acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…*Address correspondence to this author at the Dipartimento di Chimica e Chimica Industriale, Università di Pisa, 56124 Pisa, Italy; Tel/Fax: ++39-0502219282, +0-000-000-0000; E-mail: fabio.bellina@unipi.it To date, most functionalizations of (hetero)aromatic systems are achieved through the use of methods that require a preactivation of a sp2 carbon atom by halogenation or metallation. Among these, the reactions of Suzuki, [1][2][3][4][5][6][7] Negishi, [8][9][10] and Migita-Stille [11][12][13][14] foresee the creation of the new C-C bond by cross-coupling of organic halides with organometallic compounds in the presence of catalysts based on transition metals. [15][16][17] These procedures, although often characterized by high efficiency and selectivity, have two significant disadvantages: a) the activation of both reagents, which leads to an increase in the stages of the synthetic sequence, and b) the nature and quantity of reaction waste, which is detrimental to the atom economy of the entire synthetic process.…”
Section: Introductionmentioning
confidence: 99%